Reading Heliodorus' Aethiopica - Repath, Ian; Whitmarsh, Tim (Oxford University Press, 2022)
Focusing on the latest, longest, and greatest of the ancient Greek romances, this volume exploring Heliodorus' Aethiopica brings together fifteen established experts, each exploring a passage or section of the text in depth.
This edition also issued in print: 2022. - Includes bibliographical references and index. - Description based on online resource; title from PDF title page (viewed on March 7, 2022)
Keywords: Heliodorus -- of Emesa -- Aethiopica; Aufsatzsammlung; Heliodorus <Emesenus> / Aethiopica